2014
DOI: 10.1186/1471-2253-14-13
|View full text |Cite
|
Sign up to set email alerts
|

Risk over time and risk factors of intraoperative respiratory events: a historical cohort study of 14,153 children

Abstract: BackgroundThe variation in the rate of intraoperative respiratory events (IRE) over time under anesthesia and the influence of anesthesia-related factors have not yet been described. The objectives of this study were to describe the risk over time and the risk factors for IRE in children at a tertiary care hospital in southern Thailand.MethodsThe surveillance anesthetic database and chart review of IRE of 14,153 children who received surgery at Songklanagarind Hospital during January 2005 to December 2011 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Accordingly, only cardiac but not syndromic disease was identified as an independent risk factor for severe complications by multivariate logistic regression. Although we found a nonsignificant association with severe complications and higher ASA‐PS scores, the application of this risk assessment tool remains controversial in pediatric populations as there have been highly variable findings with other pediatric subpopulations . Only one further study has used the ASA‐PS score for the risk assessment in pediatric bronchoscopy, showing that children with ASA‐PS scores of I‐II had fewer unplanned events (18%) than children with scores of III (55.6%) .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Accordingly, only cardiac but not syndromic disease was identified as an independent risk factor for severe complications by multivariate logistic regression. Although we found a nonsignificant association with severe complications and higher ASA‐PS scores, the application of this risk assessment tool remains controversial in pediatric populations as there have been highly variable findings with other pediatric subpopulations . Only one further study has used the ASA‐PS score for the risk assessment in pediatric bronchoscopy, showing that children with ASA‐PS scores of I‐II had fewer unplanned events (18%) than children with scores of III (55.6%) .…”
Section: Discussionmentioning
confidence: 60%
“…Although we found a nonsignificant association with severe complications and higher ASA-PS scores, the application of this risk assessment tool remains controversial in pediatric populations as there have been highly variable findings with other pediatric subpopulations. [30][31][32] Only one further study has used the ASA-PS score for the risk assessment in pediatric bronchoscopy, showing that children with ASA-PS scores of I-II had fewer unplanned events (18%) than children with scores of III (55.6%). 21 Of note, children with scores of IV or V had even fewer adverse events (7.4%) in this analysis.…”
Section: Analysis Of Risk Factors For Complicationsmentioning
confidence: 99%
“…Deep sedation and general anesthesia are known to increase the propensity for airway obstruction and collapse . This is generally a result of increased upper airway reflex sensitivity during anesthesia .…”
Section: Discussionmentioning
confidence: 99%
“…Deep sedation and general anesthesia are known to increase the propensity for airway obstruction and collapse. 62,63 This is generally a result of increased upper airway reflex sensitivity during anesthesia. 64 Contributors to these reflexes include: mechanical contact to the laryngeal airway, which induces reflex inhibition of breathing, coughing and bronchospasm; neural efferents from the pressure receptors in the wall of the upper airways, which form a neural loop; and stimulation of the superior laryngeal nerve, which results in glottic closure and laryngospasm.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in close agreement with the findings of Dante Ranieri Junio et al [ 46 ]. However, some studies have found that the LMA has a higher risk of inducing laryngospasms than does ETT [ 41 , 47 , 48 ]. It has been speculated that this increased risk is caused by the use of the LMA or by accumulated secretions that may be a potent stimulus to the airway.…”
Section: Discussionmentioning
confidence: 99%